Tuberculosis shoulder: a diagnostic dilemma - Naik, Avinash; Pandey, Meenakshi; Mohanty, Sundar Narayan (International Journal of Research in Orthopaedics, 2020)
Tuberculosis of the shoulder can be difficult to diagnose in the early stages. If not diagnosed early, bony tuberculosis may reduce quality of life. Therefore, tuberculosis should be suspected in cases of long standings pain in the shoulder. we report a case of a female patient presenting to us after 18 months of initiations of symptoms suggestive of periarthritis of shoulder. Failure of conservative therapy and worsening of symptoms she needed further investigation and surgical management. With Biopsy she was diagnosed tuberculosis shoulder, TB shoulder to be a case of tuberculosis shoulder. The patient had a good recovery functionally following debridement and ATT. Thus, TB shoulder can also present as a case of periarteritis shoulder making its diagnosis at early stages difficult.